Torsional oscillation-considered mode transition coordinated control for a power-split PHEV based on action dependent heuristic dynamic programming. (July 2022) - Wang, Feng; Zhang, Jian; Xu, Xing; Cai, Yingfeng; Ni, Shaoyong; Que, Hongbo
Abstract: The mode transition process (MTP) from electric mode to hybrid electric mode (EM-to-HM) will cause the deterioration in occupant comfort of PHEV, to tickle this issue, a torsional oscillation-considered mode transition coordinated control strategy and a novel general evaluation index for MTP are developed in this research, the quality of mode transition and transient torsional oscillation of gears (TTOGs) during MTP are taken into consideration comprehensively. An action dependent heuristic dynamic programming algorithm which takes the vehicle jerk, friction loss and TTOGs as evaluation index is used to optimize the pressure curve of clutch oil and the compensation torque of motor in the entire EM-to-HM process. Finally, the simulation results and hardware-in-the-loop tests show that vehicle jerk and TTOGs are suppressed, and the driving comfort can be improved accordingly. Highlights: Torsional dynamic model of PCHT with angle-varying mesh stiffness and pulsating torque. Novel general assessing index for mode transition process. Torsional oscillation-considered mode transition coordinated control designed.